1352. A Computational Approach for Exploring the Binding Mechanism of Chebulinic Acid on Herpes Simplex Virus-2 and Its Implication on Chikungunya and Dengue. (26th November 2018) - Thomas, Naiju; Kumar, Sandeep; Kumar, Vikas; Tapryal, Suman
Abstract: Background: Chebulinic acid (CA), a natural compound isolated from the tree Terminalia chebula, was recently reported to have shown antiviral activity against Herpes simplex virus-2 (HSV-2). The study showed inhibition activity of CA, preventing the attachment of HSV-2 on the host cells. This activity was speculated to be due to an interaction between CA and viral surface glycoproteins, triggering alterations in its function or making virus particles inert and preventing their attachment to host cells. However, the mechanism of this inhibition was not established. The current study was designed not only to help gain insights of the mechanism of action of CA on HSV-2, but also to computationally check its binding affinity on other enveloped arboviruses, i.e., Chikungunya (ChikV) and Dengue (DenV). Methods: The viral surface glycoproteins of HSV-2, ChikV, and DenV were subjected to molecular docking with CA using the software, AutoDock Vina. Protein–protein docking was performed with ClusPro online server to elucidate the specific site and residues involved in binding between viral protein and human host receptors. Due to unavailability of crystal structure of Prohibitin, a human receptor for ChikV, structural modeling was performed with i-Tasser server. Results: The conformations obtained after docking showed good hydrogen bond interactions with a docking energy of −9.3, −8.1, and −8.8 kcal/mol against HSV-2, ChikV, and DenV, respectively. In all three viruses, CA was found to bind specifically at the site directly involved in host attachment, suggesting a possible mechanism of action by which CA inhibits the viral attachment that is consistent with the result obtained from the in vitro experiment on HSV-2. Hence the natural bio-molecule Chebulinic acid has the potential to inhibit the host attachment step of HSV-2, ChikV, and DenV by directly binding to their viral glycoproteins. Conclusion: Chebulinic acid shows a good propensity as an antiviral agent, capable of acting against multiple enveloped viruses. Additionally, a more potent and specific drug can be designed on the template of CA by process of molecular modification. Disclosures: N. Thomas, Department of Science and Technology: Government of India funding agency, Salary. S. Kumar, University Grants Commission: Government of India funding agency, Educational grant. V. Kumar, University Grants Commission: Government of India funding agency, Educational grant. S. Tapryal, Department of Science and Technology: Government of India funding agency, Research grant.